Effect of Audio–Sonic Waves on Heat Transfer Enhancement in a Distilled Water-Based Heat Exchanger - Tetuko, Agggito Pringgo; Sari, Ayu Yuswati; Simbolon, Silviana; Sebayang, Achmad M.S.; Effendi, Nur H; Ernando, Riko; Fachredzy, Amdy; Asri, Nining S; Setiadi, Eko A; Sebayang, Perdamean (UI Scholars Hub, 2025)
In this research, the influence of audio–sonic waves on distilled water used as the working fluid in a shell-and-tube heat exchanger was examined. The audio–sonic wave frequencies and flow rates of the cold and hot liquids were varied as follows: 4.85, 6.78, and 13.43 kHz for the audio–sonic waves; 0.3, 0.4, and 0.5 l/min for the cold liquid; and 0.76, 1.0, and 1.5 l/min for the hot liquid. An increase in the audio–sonic wave frequency enhanced both the overall heat transfer coefficient (U) and the enhancement factor (EF). The optimum values of U and EF, measured at 300 W/m3 ·°C and 1.05, respectively, were achieved at the highest frequency of 13.43 kHz. Additionally, the flow rates of the hot and cold liquids in the heat exchanger significantly influenced the optimal values of U and EF.